Performance Analysis BPBD Kabupaten Gresik dengan Pendekatan Key Performance Indicator (KPI) - Cahyadi, Nur; Aslamiyah, Suaibatul (Jurnal Manajerial, 2023)
Background – Gresik Regency is one of the regencies located in East Java Province which is influenced by various factors that cause various kinds of disasters, both natural and human disasters, namely demographic, geographical, hydrological and geological factors, which can cause environmental damage and cause loss of property and property. In 2021, the spotlight relating to the performance of the Gresik Regency BPBD is the news in the mass media where the Minister of Social Affairs, namely Mrs. Risma's annoyance, saw that there were residents who were victims of the rain-flood disaster which resulted in residents getting cold and forced to set up makeshift tents with tarpaulins on the side of the village road. The Social Minister's annoyance raised doubts about the performance of the Gresik Regency BPBD in the process of disaster prevention and management, especially floods. Aim – to find out the performance of BPBD Gresik Regency in the process of overcoming and preventing natural disasters, especially floods in 2021 using the Key Performance Indicator (KPI) approach. Design / methodology / approach – The method used in this study is descriptive qualitative so it is necessary to collect data from the field results needed to support this research. After the data has been collected, it is necessary to reduce the data or summarize according to the information obtained, which is then displayed or presented in accordance with the performance indicators of BPBD Gresik Regency. To strengthen the research results, it is necessary to test the validity of the data using the source triangulation method through member checks. Findings – The achievement of the performance of the Regional Disaster Management Agency (BPBD) of Gresik Regency obtained results with good criteria but the results were still not optimal. BPBD Gresik Regency cooperates with stakeholders in the context of providing services and handling of natural disasters that occur. In addition, BPBD has conducted training activities in the context of disaster prevention and mitigation. Meanwhile, in terms of responsiveness, BPBD Gresik Regency is categorized as good, because it has handled emergency actions quickly and spontaneously in carrying out aid, rescue, search and health services and social services for residents affected by disasters or as victims of disasters. Meanwhile, in terms of accountability, it was found that the BPBD of Gresik Regency had been carried out in accordance with existing and applicable standards. Research implication – Based on the results of the conclusions obtained, it is hoped that the Gresik Regency Regional Disaster Management Agency (BPBD) can continue to improve performance in accordance with the Key Performance Indicator (KPI) and the planned activities to be implemented. The need for special management to deal with disasters that are located quite far from the district BPBD office. Gresik, so as to minimize the disaster area. Tools (facilities) in disaster management must be added, equipped and modernized, because with modern and complete tools it is hoped that the disaster management process can be handled properly. as well as Human Resources (HR), in this case the Apparatus must be added and their capabilities increased, so that in the implementation of disaster management can be carried out in a professional manner.